COTTON DYEING USING ARECA CATECHU L SEED EXTRACT WITH COCONUT WATER MORDAN - Adriani, Adriani; Putri, Azizah Dwi; Novrita, Sri Zulvia; Nelmira, Weni (Universitas Negeri Yogyakarta, 2024)
The phenomenon of the textile industry in Indonesia is that there are a lot of synthetic dyes that are used as dyes in textiles, but these synthetic dyes have carcinogenic properties and can pollute the environment. To overcome this bad impact by using natural dyes. The aim of the research was to describe the color name (hue), light darkness (value), color evenness, and washing resistance using young coconut mordant water. This research uses an experimental method with primary data sources. The data collection technique uses an instrument in the form of an assessment sheet. The data analysis technique is using the Friedman K-Related sample test with the help of SPSS. The results of the research show 1) The names of the colors that appear are Sepia Brown and Cocoa Brown, 2) The dark light obtained is quite light and light, 3) The evenness of the color obtained is quite even and even, 4) The durability of washing without mordant always changes from each washing stage, and the young coconut water mordant changed at 3 and 5 washings.